2005
DOI: 10.1099/vir.0.80982-0
|View full text |Cite
|
Sign up to set email alerts
|

Koi herpesvirus represents a third cyprinid herpesvirus (CyHV-3) in the family Herpesviridae

Abstract: The sequences of four complete genes were analysed in order to determine the relatedness of koi herpesvirus (KHV) to three fish viruses in the family Herpesviridae: carp pox herpesvirus (Cyprinid herpesvirus 1, CyHV-1), haematopoietic necrosis herpesvirus of goldfish (Cyprinid herpesvirus 2, CyHV-2) and channel catfish virus (Ictalurid herpesvirus 1, IcHV-1). The genes were predicted to encode a helicase, an intercapsomeric triplex protein, the DNA polymerase and the major capsid protein. The results showed th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
166
0
2

Year Published

2006
2006
2014
2014

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 187 publications
(173 citation statements)
references
References 20 publications
3
166
0
2
Order By: Relevance
“…Although mortalities can be evoked in carp fry (Sano et al 1991), in general the effect of the disease on its host is limited and is primarily a problem in the cultivation of ornamental carp because of the focal epidermal hyperplasia. On the other hand, koi herpesvirus disease (KHVD) is a recently emerging and lethal disease of koi and common carp, with cyprinid herpesvirus 3 (CyHV-3) as the causative agent (Waltzek et al 2005(Waltzek et al , 2009. Since the first description of KHVD by Hedrick et al (1999), the virus has rapidly emerged at a global scale (Haenen et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Although mortalities can be evoked in carp fry (Sano et al 1991), in general the effect of the disease on its host is limited and is primarily a problem in the cultivation of ornamental carp because of the focal epidermal hyperplasia. On the other hand, koi herpesvirus disease (KHVD) is a recently emerging and lethal disease of koi and common carp, with cyprinid herpesvirus 3 (CyHV-3) as the causative agent (Waltzek et al 2005(Waltzek et al , 2009. Since the first description of KHVD by Hedrick et al (1999), the virus has rapidly emerged at a global scale (Haenen et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…All PCR methods that have been developed to date to detect cyprinid herpesvirus 3 (CyHV-3, Waltzek et al 2005), commonly known as koi herpesvirus (KHV), are highly sensitive and specific for the virus (Gilad et al 2002, Gray et al 2002, Bercovier et al 2005, Yuasa et al 2005. Given the relative resilience of DNA to degradation, PCR assays of KHV DNA extracted from viral capsids are generally successful, even when using tissues that have started to decompose (authors' unpubl.…”
Section: Introductionmentioning
confidence: 99%
“…Recent work has shown that two structural genes contributing to capsid architecture in other known herpesviruses are conserved in KHV, and two other genes encoding proteins involved in DNA replication are closely related to those seen in other cyprinid herpesviruses (CyHV-1 and CyHV-2) (Waltzek et al, 2005). Interestingly, since the worldwide emergence of KHV, several other viruses FIGURE 2.…”
mentioning
confidence: 99%